Impact of Foreign Direct Investment (FDI) on Economic Growth: A Study of Brazil - Fernandes, Arthur (International Journal of Economics, 2024)
Purpose: The aim of the study was to investigate the impact of foreign direct investment (FDI) on economic growth: a study of Brazil Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on Foreign Direct Investment (FDI) and economic growth in Brazil found a positive relationship between FDI inflows and GDP growth. FDI contributes to capital accumulation, technology transfer, and sectoral diversification, enhancing competitiveness. However, the impact varies across regions and industries, with disparities in spillover effects. Targeted policies are needed to maximize FDI benefits and promote inclusive growth, addressing regional disparities and socio-economic inequalities. Unique Contribution to Theory, Practice and Policy: Dependency theory, modernization theory & institutional theory may be used to anchor future studies on the impact of foreign direct investment (FDI) on economic growth: a study of Brazil. The study should provide practical recommendations for firms and corporate boards to enhance their corporate governance practices based on empirical findings. The study should inform policymakers and regulatory authorities about the implications of corporate governance regulations on firm performance and market competitiveness.